Factor price distortions, environmental regulation and innovation efficiency: An empirical study on China's power enterprises. (May 2022) - Qiao, Sen; Zhao, Dong Hao; Guo, Zi Xin; Tao, Zhang
Abstract: Strengthening environmental regulation is an important measure to solve energy and environmental problems in the process of factor pricing reform in China. Using fixed effect and system-GMM models, this paper explores the impact of factor price distortions and environmental regulation on innovation efficiency of 59 listed power enterprises in China from 2005 to 2019. The results show that: In the direct path, both capital and labor price distortions inhibit innovation efficiency, and the inhibitory effect of labor price distortions in state-owned power enterprises is more significant. For the indirect path, both economical and supervised environmental regulation promote the innovation efficiency of state-owned and non-state-owned power enterprises, while legal environmental regulation is the opposite, which shows that environmental regulation has significant "cost effect" and "rebound effect". In addition, economical, legal and supervised environmental regulation have positive moderating effects on the relationship between capital price distortions, labor price distortions and innovation efficiency, which alleviates the inhibitory effect of capital and labor price distortions on innovation efficiency. Furthermore, economical and supervised environmental regulation have significant positive moderating effects on both state-owned and non-state-owned power enterprises, while the positive moderating effect of legal environmental regulation is only in non-state-owned power enterprises. Highlights: Both CPDs and LPDs inhibit IE. The inhibitory effect of LPDs in SOEs is more significant. ER has significant "cost effect" and "rebound effect". ERA, ERB and ERC alleviates the inhibitory effect of CPDs and LPDs on IE. Formulate differentiated ER policies to improve the IE of power enterprises.